Social Science Research in the Arab World and Beyond A Guide for Students, Instructors and Researchers - Tessler, Mark (SpringerBriefs in Sociology, 2023)
This book presents and discusses the logic and method of social science research adapted mainly for instruction at Arab universities and for research in Arab countries, but with applicability beyond the region. It illustrates major concepts and methods pertaining to research with examples of previous studies carried out in the Arab world and with exercises using Arab Barometer and other datasets. The book situates itself between a regular methods textbook and an annotated list of major concepts and methods, and includes an introduction, three chapters, and four appendices.